Analisis Hadis Berkaitan Nama Lain Bagi Surah Al-Mulk Dalam Kursus Tafsir Maudu‘i Di USIM: Satu Kajian Tinjauan - Abdulloh Salaeh; Amran Abdul Halim; Syed Najihuddin Syed Hassan; Nidzamuddin Zakaria; Mahsor Yahya; Walid Mohd Said (Penerbit KUIPSAS, 2024)
Non-Indexed Publication